Adopting Genre Based Approach To Improve Students' English Writing Skill Of The Twelfth Year Students Of SMA Muhammadiyah 1 Klaten Academic Year 2009/2010 - Supriyadi, Agus (2012)
One of the obvious problems found in SMA Muhammadiyah 1 Klaten was the fact that the students' English writing skill was still low. It was indicated with the low score achieved by the students in the English writing test. To improve it, classroom action research was purposely done. The research was carried out in SMA Muhammadiyah 1 Klaten from May to December 2010. The subject of the research was 35 students of the twelfth year science class one consisting of 14 male and 22 female students. This action research was conducted in two cycles. Each consisted of planning, acting, observing, and reflecting. In the first cycle, the researcher implemented genre based approach with four stages i.e. building knowledge of the field, modeling of text, joint construction of text, and independent construction of text. In the second cycle, the researcher applied grammar translation method with three stages i.e. presentation, practice, and production. The second cycle was purposely done because of the fact that the score of grammar was still low. To collect the data the researcher used tests, interview, observation, and documentation. To validate quantitative data, the researcher used internal validity and reliability as well as inter-rater reliability. To validate qualitative data, the researcher used data triangulation. To analyze quantitative data, the researcher applied t-test for non independent. To analyze qualitative data, the researcher used flow model of analysis. The research findings of the first cycle, in which genre based approach was implemented, revealed that there was significant improvement of average score between before and after being given treatment. For that reason, the hypothesis stating that using genre based approach is able to improve students' English writing skill proved right. Besides, the teaching and learning process could run more interactively and attractively. As a result, the students were able to understand and do as the teacher instructed better. For those reasons, the researcher's hypothesis stating that there are benefits when genre based approach is implemented in the classroom practice proved correct. The research findings of the second cycle, in which grammar translation method was implemented, showed great improvement especially for grammar scores. For that reason, grammar translation method was really able to back up genre based approach to improve students' English writing skill. Based on the result of the research, the researcher suggests the English teachers to use genre based approach backed up with grammar translation method appropriately and creatively. For the students, it is suggested to follow what the teacher instructs obediently, critically and creatively. For the school, it is suggested to conduct training for English teachers to understand more about genre based approach as well as to refresh about grammar translation method and to complete the school with necessary facilities and equipment.